High-hardness and low-friction multi-layer composite cutter coating and preparation method thereof

By depositing multi-layer composite coating on the tool, combined with alternating deposition technology of hard support layer and friction reducing layer, the problem of high friction coefficient of TiSiN coating under dry friction conditions is solved, and a tool coating with high hardness and low friction is achieved, extending the service life of the tool.

CN119615077APending Publication Date: 2025-03-14化学与精细化工广东省实验室潮州分中心 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411834443.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing TiSiN coating has a high friction coefficient under dry friction conditions, resulting in severe wear and failure during high-speed cutting.

Method used

A multi-layer composite coating structure is adopted, including single-sided polished silicon wafers or YG8 cemented carbide as the substrate, and the base layer, transition layer and composite deposited layer are deposited in turn. The composite deposition layer is alternately deposited by a hard support layer and a friction reducing layer, and is prepared by a shared technology of multi-arc ion plating and high-power pulse magnetron sputtering.

Benefits of technology

A multi-layer composite tool coating with high hardness and low friction coefficient is achieved, which enhances the bonding force between the coating and the substrate, reduces the internal stress of the coating, and extends the service life of the tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615077A_ABST
    Figure CN119615077A_ABST
Patent Text Reader

Abstract

The invention discloses a high-hardness and low-friction multi-layer composite cutter coating and a preparation method thereof.The high-hardness and low-friction multi-layer composite cutter coating is prepared through a multi-arc ion plating and high-power pulse magnetron sputtering co-deposition technology and structurally comprises a Ti base layer, a TiN transition layer, a TiSiN hard supporting layer and a TiSi-DLC anti-friction layer, and the TiSiN hard supporting layer and the TiSi-DLC anti-friction layer are alternately deposited. According to the high-hardness and low-friction multi-layer composite cutter coating and the preparation method thereof, through the alternate deposition design of the coating, the internal stress between layers is effectively balanced, the binding force between the coating and a base body is improved, the surface modification requirement of an industrial cutting tool is met, meanwhile, the comprehensive mechanical property of the coating is further improved by changing the modulation period, and the service life of the coating is prolonged. The popularization value is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating materials, and in particular relates to a high-hardness, low-friction multilayer composite tool coating and a preparation method thereof. Background Art

[0002] With the rapid development of the machinery manufacturing industry, the cutting environment of tools is becoming increasingly diversified. Strict processing requirements and cost control have promoted the advancement of tool coating technology. Compared with traditional tool coatings such as TiN and CrN, TiSiN coating has better mechanical properties and high-temperature thermal stability, which makes it have great application potential in the field of tool coating. However, under dry friction conditions, the friction coefficient of TiSiN coating is as high as 0.8 to 1.0, which causes severe wear during high-speed cutting and premature failure.

[0003] DLC coating is a carbonaceous coating that has attracted much attention due to its excellent tribological properties. Its dry friction coefficient in air is less than 0.1 and its wear rate is less than 10 −6 mm 3 / N·m. In addition, researchers have proposed many methods to address the high internal stress generated during the growth of DLC coatings and the poor coating / substrate bonding caused by the graphitization transformation of DLC coatings at high temperatures. For example, element doping is an effective solution. In the current study, the Ti element can effectively reduce the internal growth stress of the DLC coating, and the Si element has certain advantages in improving the high-temperature thermal stability of the DLC coating. TiSi co-doping significantly improves the bonding between the DLC coating and the substrate. However, due to the reduced Sp3 content, the hardness of the element-doped DLC coating is generally lower than 20 GPa, and it is difficult to meet the surface modification requirements of the tool when used alone. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a high-hardness, low-friction multilayer composite tool coating with both high strength and low friction coefficient and a preparation method thereof.

[0005] The technical solution of the present invention to solve the above technical problems is: A high-hardness, low-friction multi-layer composite tool coating is based on a single-sided polished silicon wafer and / or YG8 cemented carbide as a substrate, and a primer layer, a transition layer and a composite deposition layer are sequentially deposited on the surface of the substrate. The composite deposition layer is formed by periodically depositing a hard support layer and a friction reduction layer in sequence for at least one cycle.

[0006] Specifically, the multi-arc ion plating and high-power pulse magnetron sputtering co-deposition technology are used for preparation.

[0007] The present invention also discloses a method for preparing the above-mentioned high-hardness, low-friction multilayer composite tool coating, comprising the following steps: Substrate treatment, cleaning the substrate, and removing organic contamination from the substrate surface; Installation of deposition equipment: Install Ti target and TiSi target on two target holders at opposite positions in the deposition chamber, install a magnetron TiSi target on another target holder in the deposition chamber, adjust the positions of Ti target and TiSi target so that the distances between Ti target and TiSi target and the substrate are the same, then place the cleaned substrate in the center of the rotating rack fixture, and close the chamber door; Pre-working environment configuration, start the rough pump valve to pump the vacuum in the deposition chamber to 7.5 Pa, switch the molecular pump, and continue to pump the deposition chamber to a heated vacuum of 5x10 -2 Pa, set the heating temperature to 350 °C, set the rotating speed to 35 Hz, and evacuate the deposition chamber to a background vacuum of 2.5x10 -2 Pa, set up the pre-working environment; Substrate etching: start the AEG etching system, adjust the argon gas flow rate, set the etching gas pressure, set the etching current parameters, and perform ion etching on the substrate surface step by step; Depositing the bottom layer: after the substrate etching is completed, argon gas is used as the working gas, the current of the Ti target and the deposition negative bias are set, and the Ti target is sputtered by multi-arc ion plating to deposit a Ti layer on the etched substrate to form a bottom layer with a thickness of 0.3 μm; Depositing the transition layer, using argon and nitrogen as working gases, sputtering a Ti target by multi-arc ion plating, depositing TiN on the base layer to form a transition layer with a thickness of 0.6 μm; Depositing a composite deposition layer, periodically sequentially using multi-arc ion plating to sputter a TiSi target to deposit a hard support layer and using high-power pulsed magnetron sputtering to sputter a magnetron TiSi target to deposit a friction reduction layer to form a composite deposition layer, wherein the cycle is at least once; After the deposition is completed, the equipment is gradually turned off, the introduction of the working gas is stopped, and the sample on the turntable fixture is taken out, and the sample is coated with the high hardness, low friction multilayer composite tool coating.

[0008] Specifically, the step of depositing the composite deposition layer includes the following steps: Depositing a hard support layer, using argon and nitrogen as working gases, turning off the Ti target, setting the current and deposition negative bias of the TiSi target, sputtering the TiSi target by multi-arc ion plating, depositing TiSiN on the transition layer, and forming a hard support layer with a thickness of 0.5-3.0 μm; Deposit the anti-friction layer, use argon and acetylene as working gas, turn off the TiSi target, set the working parameters of the magnetron TiSi target, and deposit TiSi-DLC on the hard support layer by high-power pulsed magnetron sputtering of the magnetron TiSi target to form an anti-friction layer with a thickness of 0.1~0.6 μm.

[0009] Specifically, in the substrate processing step, the substrate is composed of a single-side polished silicon wafer and / or YG8 cemented carbide, and the substrate is ultrasonically cleaned twice in acetone and alcohol, each time for 20 minutes, then rinsed with deionized water, and finally dried with nitrogen.

[0010] Specifically, in the deposition equipment installation step, the Ti target used is a pure titanium target with a purity of 99.8%, the TiSi target used is an alloy target with an atomic percentage composition of Ti:Si=90:10, and the magnetron TiSi target used is an alloy target with an atomic percentage composition of Ti:Si=75:25.

[0011] Specifically, in the substrate etching step, the argon gas flow rate is 100 sccm, the etching gas pressure is 0.42 Pa, and the etching current parameters are 50 A for ion cleaning and 15 to 20 A for anode.

[0012] Specifically, in the step of depositing the base layer, the Ti target current is set to 130 A, the deposition negative bias voltage is 150 V, the argon gas flow rate is 100 sccm, and the deposition time is 15 min; in the step of depositing the transition layer, the Ti target current is set to 130 A, the deposition negative bias voltage is 150 V, the argon gas flow rate is 80 sccm, the nitrogen gas flow rate is 200 sccm, and the deposition time is 15 min.

[0013] Specifically, in the step of depositing the hard support layer, the TiSi target current is 130 A, the deposition negative bias voltage is 150 V, the argon flow rate is 80 sccm, the nitrogen flow rate is 200 sccm, and the deposition time is 18.3-110 min.

[0014] Specifically, in the step of depositing the friction-reducing layer, the working parameters of the magnetron TiSi target are a constant power of 4 Kw, a deposition duty cycle of 10%, a deposition negative bias of 130 V, an argon flow rate of 110 sccm, an acetylene flow rate of 15 sccm, and a deposition time of 8 to 48 min.

[0015] The present invention has the following beneficial effects: (1) High-power pulsed magnetron sputtering and multi-arc ion plating co-deposition technology is used to combine the advantages of the two technologies to reduce coating defects and improve coating quality.

[0016] (2) Depositing a Ti base layer and a TiN transition layer on the substrate surface provides a good bond between the composite deposited layer and the substrate, ensuring that the composite deposited layer has a better deposition effect; (3) The Ti / Si elements added to the DLC layer in the friction-reducing layer weaken the internal stress in the layer and increase the bonding force with the TiSiN hard support layer; (4) The composite deposited layers can effectively balance the internal stress between layers due to the alternating deposition, thus enhancing the bonding force between the high-hardness, low-friction multilayer composite tool coating and the substrate; (5) Compared with single-layer TiSiN and TiSi-DLC coatings, this high-hardness, low-friction multilayer composite tool coating combines the advantages of both, with high hardness and low friction coefficient, and has great production promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the cross-sectional SEM morphology of the product prepared in Example 1 of the present invention.

[0018] Figure 2 This is the cross-sectional SEM morphology of the product prepared in Example 2 of the present invention.

[0019] Figure 3 This is the cross-sectional SEM morphology of the product prepared in Example 3 of the present invention.

[0020] Figure 4 This is the cross-sectional SEM morphology of the product prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0021] The present invention is described in detail below with reference to the embodiments.

[0022] A high-hardness, low-friction multi-layer composite tool coating, with a single-side polished silicon wafer and / or YG8 cemented carbide as a substrate, a primer layer, a transition layer and a composite deposition layer are sequentially deposited on the surface of the substrate, and the composite deposition layer is formed by periodically depositing a hard support layer and a friction-reducing layer in sequence for at least one period. Specifically, it is prepared by multi-arc ion plating and high-power pulsed magnetron sputtering co-deposition technology. Example

[0023] A method for preparing a high-hardness, low-friction multilayer composite tool coating according to Example 1 of the present invention comprises the following steps: Substrate treatment: cleaning the substrate. The substrate composed of single-side polished silicon wafer and / or YG8 cemented carbide is ultrasonically cleaned in acetone and alcohol twice, each time for 20 min, then rinsed with deionized water, and finally dried with nitrogen to ensure that there is no organic contamination on the substrate surface during the deposition process and to ensure the deposition effect.

[0024] The deposition equipment is installed, a Ti target and a TiSi target are installed on target holders at two relative positions in a deposition chamber, a magnetron TiSi target is installed on another target holder in the deposition chamber, the positions of the Ti target and the TiSi target are adjusted so that the distances between the Ti target and the TiSi target and the substrate are the same, and then the cleaned substrate is placed in the center of a turntable fixture, and the chamber door is closed; specifically, the Ti target used is a pure titanium target with a purity of 99.8%, the TiSi target used is an alloy target with an atomic percentage composition of Ti:Si=90:10, and the magnetron TiSi target used is an alloy target with an atomic percentage composition of Ti:Si=75:25.

[0025] Pre-working environment configuration, start the rough pump valve to pump the vacuum in the deposition chamber to 7.5 Pa, switch the molecular pump, and continue to pump the deposition chamber to a heated vacuum of 5x10 -2 Pa, set the heating temperature to 350 °C, set the rotating speed to 35 Hz, and evacuate the deposition chamber to a background vacuum of 2.5x10 -2 Pa, set up the pre-working environment.

[0026] For substrate etching, start the AEG etching system, adjust the argon flow rate to 100 sccm, set the etching gas pressure to 0.42 Pa, set the etching current parameters to ion cleaning 50 A and anode 15 ~ 20 A, and perform ion etching on the substrate surface step by step.

[0027] Deposit the base layer. After the substrate etching is completed, argon is used as the working gas with an argon flow rate of 100 sccm. The current of the Ti target is set to 130 A and the deposition negative bias is set to 150 V. The Ti target is sputtered by multi-arc ion plating to deposit a Ti layer on the etched substrate. The deposition time is 15 min to form a base layer with a thickness of 0.3 μm.

[0028] The transition layer was deposited with argon and nitrogen as working gases, the argon flow rate was 80 sccm, and the nitrogen flow rate was 200 sccm. TiN was deposited on the base layer by sputtering a Ti target by multi-arc ion plating for 15 min to form a transition layer with a thickness of 0.6 μm.

[0029] The hard support layer was deposited with argon and nitrogen as working gases, the argon flow rate was 80 sccm, the nitrogen flow rate was 200 sccm, the Ti target was turned off, the current of the TiSi target was set to 130 A and the deposition negative bias was set to 150 V, and TiSiN was deposited on the transition layer by multi-arc ion plating sputtering of the TiSi target for 110 min to form a hard support layer with a thickness of 3.0 μm.

[0030] The anti-friction layer was deposited with argon and acetylene as working gases, the argon flow rate was 110 sccm, the acetylene flow rate was 15 sccm, the TiSi target was turned off, the constant power of the magnetron TiSi target was set to 4 kW, the deposition duty cycle was 10%, the deposition negative bias was 130 V, and TiSi-DLC was deposited on the hard support layer by high-power pulsed magnetron sputtering of the magnetron TiSi target. The deposition time was 48 min, and a friction-reducing layer with a thickness of 0.6 μm was formed.

[0031] In this embodiment, the number of cycles for depositing the composite deposition layer is 1, that is, the step of depositing the hard support layer and the step of depositing the anti-friction layer are periodically deposited in sequence once.

[0032] After the deposition is completed, the equipment is gradually turned off, the introduction of the working gas is stopped, and the sample on the turntable fixture is taken out, and the sample is coated with the high hardness, low friction multilayer composite tool coating. Example

[0033] A method for preparing a high-hardness, low-friction multilayer composite tool coating according to Example 2 of the present invention comprises the following steps: Substrate treatment: cleaning the substrate. The substrate composed of single-side polished silicon wafer and / or YG8 cemented carbide is ultrasonically cleaned twice in acetone and alcohol for 20 minutes each time, then rinsed with deionized water, and finally dried with nitrogen to ensure that there is no organic contamination on the substrate surface during the deposition process and to ensure the deposition effect.

[0034] The deposition equipment is installed, a Ti target and a TiSi target are installed on target holders at two relative positions in a deposition chamber, a magnetron TiSi target is installed on another target holder in the deposition chamber, the positions of the Ti target and the TiSi target are adjusted so that the distances between the Ti target and the TiSi target and the substrate are the same, and then the cleaned substrate is placed in the center of a turntable fixture, and the chamber door is closed; specifically, the Ti target used is a pure titanium target with a purity of 99.8%, the TiSi target used is an alloy target with an atomic percentage composition of Ti:Si=90:10, and the magnetron TiSi target used is an alloy target with an atomic percentage composition of Ti:Si=75:25.

[0035] Pre-working environment configuration, start the rough pump valve to pump the vacuum in the deposition chamber to 7.5 Pa, switch the molecular pump, and continue to pump the deposition chamber to a heated vacuum of 5x10 -2 Pa, set the heating temperature to 350 °C, set the rotating speed to 35 Hz, and evacuate the deposition chamber to a background vacuum of 2.5x10 -2 Pa, set up the pre-working environment.

[0036] For substrate etching, start the AEG etching system, adjust the argon flow rate to 100 sccm, set the etching gas pressure to 0.42 Pa, set the etching current parameters to ion cleaning 50 A and anode 15 ~ 20 A, and perform ion etching on the substrate surface step by step.

[0037] Deposit the base layer. After the substrate etching is completed, argon is used as the working gas with an argon flow rate of 100 sccm. The current of the Ti target is set to 130 A and the deposition negative bias is set to 150 V. The Ti target is sputtered by multi-arc ion plating to deposit a Ti layer on the etched substrate. The deposition time is 15 min to form a base layer with a thickness of 0.3 μm.

[0038] The transition layer was deposited with argon and nitrogen as working gases, the argon flow rate was 80 sccm, and the nitrogen flow rate was 200 sccm. TiN was deposited on the base layer by sputtering a Ti target by multi-arc ion plating for 15 min to form a transition layer with a thickness of 0.6 μm.

[0039] The hard support layer was deposited with argon and nitrogen as working gases, the argon flow rate was 80 sccm, the nitrogen flow rate was 200 sccm, the Ti target was turned off, the current of the TiSi target was set to 130 A and the deposition negative bias was set to 150 V, and TiSiN was deposited on the transition layer by sputtering the TiSi target by multi-arc ion plating. The deposition time was 55 min to form a hard support layer with a thickness of 1.5 μm.

[0040] The anti-friction layer was deposited with argon and acetylene as working gases, the argon flow rate was 110 sccm, the acetylene flow rate was 15 sccm, the TiSi target was turned off, the constant power of the magnetron TiSi target was set to 4 kW, the deposition duty cycle was 10%, the deposition negative bias was 130 V, and TiSi-DLC was deposited on the hard support layer by high-power pulsed magnetron sputtering of the magnetron TiSi target. The deposition time was 24 min, and a friction-reducing layer with a thickness of 0.3 μm was formed.

[0041] In this embodiment, the number of cycles for depositing the composite deposition layer is 2 times, that is, the step of depositing the hard support layer and the step of depositing the friction-reducing layer are periodically deposited in sequence for 2 times.

[0042] After the deposition is completed, the equipment is gradually turned off, the introduction of the working gas is stopped, and the sample on the turntable fixture is taken out, and the sample is coated with the high hardness, low friction multilayer composite tool coating. Example

[0043] A method for preparing a high-hardness, low-friction multilayer composite tool coating according to Example 3 of the present invention comprises the following steps: Substrate treatment: cleaning the substrate. The substrate composed of single-side polished silicon wafer and / or YG8 cemented carbide is ultrasonically cleaned twice in acetone and alcohol for 20 minutes each time, then rinsed with deionized water, and finally dried with nitrogen to ensure that there is no organic contamination on the substrate surface during the deposition process and to ensure the deposition effect.

[0044] The deposition equipment is installed, a Ti target and a TiSi target are installed on target holders at two relative positions in a deposition chamber, a magnetron TiSi target is installed on another target holder in the deposition chamber, the positions of the Ti target and the TiSi target are adjusted so that the distances between the Ti target and the TiSi target and the substrate are the same, and then the cleaned substrate is placed in the center of a turntable fixture, and the chamber door is closed; specifically, the Ti target used is a pure titanium target with a purity of 99.8%, the TiSi target used is an alloy target with an atomic percentage composition of Ti:Si=90:10, and the magnetron TiSi target used is an alloy target with an atomic percentage composition of Ti:Si=75:25.

[0045] Pre-working environment configuration, start the rough pump valve to pump the vacuum in the deposition chamber to 7.5 Pa, switch the molecular pump, and continue to pump the deposition chamber to a heated vacuum of 5x10 -2 Pa, set the heating temperature to 350 °C, set the rotating speed to 35 Hz, and evacuate the deposition chamber to a background vacuum of 2.5x10 -2 Pa, set up the pre-working environment.

[0046] For substrate etching, start the AEG etching system, adjust the argon flow rate to 100 sccm, set the etching gas pressure to 0.42 Pa, set the etching current parameters to ion cleaning 50 A and anode 15 ~ 20 A, and perform ion etching on the substrate surface step by step.

[0047] Deposit the base layer. After the substrate etching is completed, argon is used as the working gas with an argon flow rate of 100 sccm. The current of the Ti target is set to 130 A and the deposition negative bias is set to 150 V. The Ti target is sputtered by multi-arc ion plating to deposit a Ti layer on the etched substrate. The deposition time is 15 min to form a base layer with a thickness of 0.3 μm.

[0048] The transition layer was deposited with argon and nitrogen as working gases, the argon flow rate was 80 sccm, and the nitrogen flow rate was 200 sccm. TiN was deposited on the base layer by sputtering a Ti target by multi-arc ion plating for 15 min to form a transition layer with a thickness of 0.6 μm.

[0049] The hard support layer was deposited with argon and nitrogen as working gases, the argon flow rate was 80 sccm, the nitrogen flow rate was 200 sccm, the Ti target was turned off, the current of the TiSi target was set to 130 A and the deposition negative bias was set to 150 V, and TiSiN was deposited on the transition layer by multi-arc ion plating sputtering of the TiSi target for 27.5 min to form a hard support layer with a thickness of 0.75 μm.

[0050] The anti-friction layer was deposited with argon and acetylene as working gases, the argon flow rate was 110 sccm, the acetylene flow rate was 15 sccm, the TiSi target was turned off, the constant power of the magnetron TiSi target was set to 4 kW, the deposition duty cycle was 10%, the deposition negative bias was 130 V, and TiSi-DLC was deposited on the hard support layer by high-power pulsed magnetron sputtering of the magnetron TiSi target. The deposition time was 12 min, and a friction-reducing layer with a thickness of 0.15 μm was formed.

[0051] In this embodiment, the number of cycles for depositing the composite deposition layer is 4 times, that is, the step of depositing the hard support layer and the step of depositing the anti-friction layer are periodically deposited 4 times in sequence.

[0052] After the deposition is completed, the equipment is gradually turned off, the introduction of the working gas is stopped, and the sample on the turntable fixture is taken out, and the sample is coated with the high hardness, low friction multilayer composite tool coating. Example

[0053] A method for preparing a high-hardness, low-friction multilayer composite tool coating according to Example 4 of the present invention comprises the following steps: Substrate treatment: cleaning the substrate. The substrate composed of single-side polished silicon wafer and / or YG8 cemented carbide is ultrasonically cleaned twice in acetone and alcohol for 20 minutes each time, then rinsed with deionized water, and finally dried with nitrogen to ensure that there is no organic contamination on the substrate surface during the deposition process and to ensure the deposition effect.

[0054] The deposition equipment is installed, a Ti target and a TiSi target are installed on target holders at two relative positions in a deposition chamber, a magnetron TiSi target is installed on another target holder in the deposition chamber, the positions of the Ti target and the TiSi target are adjusted so that the distances between the Ti target and the TiSi target and the substrate are the same, and then the cleaned substrate is placed in the center of a turntable fixture, and the chamber door is closed; specifically, the Ti target used is a pure titanium target with a purity of 99.8%, the TiSi target used is an alloy target with an atomic percentage composition of Ti:Si=90:10, and the magnetron TiSi target used is an alloy target with an atomic percentage composition of Ti:Si=75:25.

[0055] Pre-working environment configuration, start the rough pump valve to pump the vacuum in the deposition chamber to 7.5 Pa, switch the molecular pump, and continue to pump the deposition chamber to a heated vacuum of 5x10 -2 Pa, set the heating temperature to 350 °C, set the rotating speed to 35 Hz, and evacuate the deposition chamber to a background vacuum of 2.5x10 -2 Pa, set up the pre-working environment.

[0056] For substrate etching, start the AEG etching system, adjust the argon flow rate to 100 sccm, set the etching gas pressure to 0.42 Pa, set the etching current parameters to ion cleaning 50 A and anode 15 ~ 20 A, and perform ion etching on the substrate surface step by step.

[0057] Deposit the base layer. After the substrate etching is completed, argon is used as the working gas with an argon flow rate of 100 sccm. The current of the Ti target is set to 130 A and the deposition negative bias is set to 150 V. The Ti target is sputtered by multi-arc ion plating to deposit a Ti layer on the etched substrate. The deposition time is 15 min to form a base layer with a thickness of 0.3 μm.

[0058] The transition layer was deposited with argon and nitrogen as working gases, the argon flow rate was 80 sccm, and the nitrogen flow rate was 200 sccm. TiN was deposited on the base layer by sputtering a Ti target by multi-arc ion plating for 15 min to form a transition layer with a thickness of 0.6 μm.

[0059] The hard support layer was deposited with argon and nitrogen as working gases, the argon flow rate was 80 sccm, the nitrogen flow rate was 200 sccm, the Ti target was turned off, the current of the TiSi target was set to 130A and the deposition negative bias was set to 150V, and TiSiN was deposited on the transition layer by sputtering the TiSi target by multi-arc ion plating. The deposition time was 18.3 min, forming a hard support layer with a thickness of 0.5 μm.

[0060] The anti-friction layer was deposited with argon and acetylene as working gases, the argon flow rate was 110 sccm, the acetylene flow rate was 15 sccm, the TiSi target was turned off, the constant power of the magnetron TiSi target was set to 4 kW, the deposition duty cycle was 10%, the deposition negative bias was 130 V, and TiSi-DLC was deposited on the hard support layer by high-power pulsed magnetron sputtering of the magnetron TiSi target. The deposition time was 8 min, and a friction-reducing layer with a thickness of 0.1 μm was formed.

[0061] In this embodiment, the number of cycles for depositing the composite deposition layer is 6 times, that is, the step of depositing the hard support layer and the step of depositing the anti-friction layer are periodically deposited 6 times in sequence.

[0062] After the deposition is completed, the equipment is gradually turned off, the introduction of the working gas is stopped, and the sample on the turntable fixture is taken out, and the sample is coated with the high hardness, low friction multilayer composite tool coating.

[0063] Comparative Example 1 This comparative example provides a TiSiN coating, which is different from Example 1 only in that the step of depositing the friction-reducing layer is removed, and the time for depositing the hard support layer is 60 min, thereby obtaining a single-layer TiSiN coating.

[0064] Comparative Example 2 This comparative example provides a TiSi-DLC coating, which is different from Example 1 only in that the step of depositing a hard support layer is removed, and the time for depositing a friction-reducing layer is 120 min, thereby obtaining a single-layer TiSi-DLC coating.

[0065] The products of Examples 1 to 4 were compared with those of Comparative Examples 1 and 2 in terms of hardness, elastic modulus and friction coefficient. The comparison results are shown in the following table.

[0066] Sample No. Hardness (GPa) Elastic modulus (GPa) Friction coefficient Example 1 23.11 269.23 0.40 Example 2 27.83 309.21 0.38 Example 3 33.22 351.52 0.33 Example 4 28.09 301.92 0.42 Comparative Example 1 30.2 330.5 0.80 Comparative Example 2 20.2 228.6 0.30 It can be seen from the data center in the above table that compared with comparative example 1, each product of the embodiment has a lower friction coefficient, which is due to the friction and lubrication effect of the TiSi-DLC friction reduction layer on the surface, that is, the products prepared in the embodiments of the present invention improve the tribological properties of the coating through a composite method. Compared with comparative example 2, each product of the embodiment has a higher hardness value, which is due to the supporting role played by the TiSiN hard support layer, that is, the products prepared in the embodiments of the present invention improve the mechanical properties of the coating through a composite method. It can be clearly seen from the above table that the product obtained in Example 3 has the highest hardness value and elastic modulus, which indicates that by changing the modulation period of the composite deposition layer, the comprehensive performance of the coating can be further improved.

[0067] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A high-hardness, low-friction multi-layer composite tool coating, with a single-side polished silicon wafer and / or YG8 cemented carbide as the substrate, characterized in that: A primer layer, a transition layer and a composite deposition layer are sequentially deposited on the surface of the substrate, wherein the composite deposition layer is formed by sequentially depositing a hard support layer and a friction reduction layer in a periodic manner for at least one cycle.

2. The high hardness, low friction multi-layer composite tool coating according to claim 1, characterized in that: The material was prepared by multi-arc ion plating and high-power pulsed magnetron sputtering co-deposition technology.

3. A method for preparing a high-hardness, low-friction multilayer composite tool coating as claimed in claim 1 or 2, characterized in that: The steps include: Substrate treatment, cleaning the substrate, and removing organic contamination from the substrate surface; Installation of deposition equipment: Install Ti target and TiSi target on two target holders at opposite positions in the deposition chamber, install a magnetron TiSi target on another target holder in the deposition chamber, adjust the positions of Ti target and TiSi target so that the distances between Ti target and TiSi target and the substrate are the same, then place the cleaned substrate in the center of the rotating rack fixture, and close the chamber door; Pre-working environment configuration, start the rough pump valve to pump the vacuum in the deposition chamber to 7.5 Pa, switch the molecular pump, and continue to pump the deposition chamber to a heated vacuum of 5x10 -2 Pa, set the heating temperature to 350 °C, set the rotating speed to 35 Hz, and evacuate the deposition chamber to a background vacuum of 2.5x10 -2 Pa, set up the pre-working environment; Substrate etching: start the AEG etching system, adjust the argon gas flow rate, set the etching gas pressure, set the etching current parameters, and perform ion etching on the substrate surface step by step; Depositing the bottom layer: after the substrate etching is completed, argon gas is used as the working gas, the current of the Ti target and the deposition negative bias are set, and the Ti target is sputtered by multi-arc ion plating to deposit a Ti layer on the etched substrate to form a bottom layer with a thickness of 0.3 μm; Depositing the transition layer, using argon and nitrogen as working gases, sputtering a Ti target by multi-arc ion plating, depositing TiN on the base layer to form a transition layer with a thickness of 0.6 μm; Depositing a composite deposition layer, periodically sequentially using multi-arc ion plating to sputter a TiSi target to deposit a hard support layer and using high-power pulsed magnetron sputtering to sputter a magnetron TiSi target to deposit a friction reduction layer to form a composite deposition layer, wherein the cycle is at least once; After the deposition is completed, the equipment is gradually turned off, the introduction of the working gas is stopped, and the sample on the turntable fixture is taken out, and the sample is coated with the high hardness, low friction multilayer composite tool coating.

4. The preparation method according to claim 3, characterized in that: The step of depositing the composite deposition layer comprises the following steps: Depositing a hard support layer, using argon and nitrogen as working gases, turning off the Ti target, setting the current and deposition negative bias of the TiSi target, sputtering the TiSi target by multi-arc ion plating, depositing TiSiN on the transition layer, and forming a hard support layer with a thickness of 0.5-3.0 μm; Deposit the anti-friction layer, use argon and acetylene as working gas, turn off the TiSi target, set the working parameters of the magnetron TiSi target, and deposit TiSi-DLC on the hard support layer by high-power pulsed magnetron sputtering of the magnetron TiSi target to form an anti-friction layer with a thickness of 0.1~0.6 μm.

5. The preparation method according to claim 3, characterized in that: In the substrate processing step, the substrate is composed of a single-side polished silicon wafer and / or YG8 cemented carbide, and the substrate is ultrasonically cleaned twice in acetone and alcohol, each time for 20 minutes, then rinsed with deionized water, and finally dried with nitrogen.

6. The preparation method according to claim 3, characterized in that: In the deposition equipment installation step, the Ti target used is a pure titanium target with a purity of 99.8%, the TiSi target used is an alloy target with an atomic percentage composition of Ti:Si=90:10, and the magnetron TiSi target used is an alloy target with an atomic percentage composition of Ti:Si=75:

25.

7. The preparation method according to claim 3, characterized in that: In the substrate etching step, the argon gas flow rate is 100 sccm, the etching gas pressure is 0.42 Pa, and the etching current parameters are 50 A for ion cleaning and 15 to 20 A for anode.

8. The preparation method according to claim 3, characterized in that: In the step of depositing the base layer, the Ti target current is set to 130 A, the deposition negative bias voltage is 150 V, the argon gas flow rate is 100 sccm, and the deposition time is 15 min; in the step of depositing the transition layer, the Ti target current is set to 130 A, the deposition negative bias voltage is 150 V, the argon gas flow rate is 80 sccm, the nitrogen gas flow rate is 200 sccm, and the deposition time is 15 min.

9. The preparation method according to claim 4, characterized in that: In the step of depositing the hard support layer, the TiSi target current is 130 A, the deposition negative bias voltage is 150 V, the argon flow rate is 80 sccm, the nitrogen flow rate is 200 sccm, and the deposition time is 18.3-110 min.

10. The preparation method according to claim 4, characterized in that: In the step of depositing the friction-reducing layer, the working parameters of the magnetron TiSi target are a constant power of 4 Kw, a deposition duty cycle of 10%, a deposition negative bias of 130 V, an argon flow rate of 110 sccm, an acetylene flow rate of 15 sccm, and a deposition time of 8 to 48 min.